(untitled) (Heritage, 2023)
The historical development of human society has consistently emphasized human rights and freedoms as fundamental principles for the emergence and evolution of a democratic and civil society. This has led to the establishment of modern public administration with a robust legal foundation and legally guided and controlled security services. In such a context, security plays a pivotal role in the existence of a cohesive society, impacting all social and economic aspects. Security services are closely linked to the state, responsible for planning, organizing, and implementing measures and activities aimed at safeguarding individuals and property from various threats. As the entities responsible for these activities within society, security service providers take administrative measures and actions to continually monitor their operations. Therefore, administrative monitoring of security services is of paramount importance for the functioning and transparency of the state’s security apparatus. Given the predominantly confidential nature of security service activities, it becomes essential for the public to have assurances that the means employed to carry out these activities are used correctly, legally, economically, and efficiently. This paper primarily focuses on identifying the specifics of administrative monitoring of the security services in the Republic of Serbia as defined by the norms established in system laws and related regulations. In conclusion, this work underscores that administrative monitoring essentially entails an ongoing process of external and internal supervision and control over the execution of daily tasks and responsibilities of security services. This oversight is achieved through the implementation of appropriate administrative actions and measures, the effectiveness of which is instrumental in realizing the powers and authorities defined by law.